Pengaruh Pendidikan, Upah, dan Kesempatan Kerja Terhadap Pengangguran di Provinsi Bali - Alfandi Djunaidi Putra; I Wayan Sukadana (Jurnal Sains dan Ilmu Terapan, 2024)
In Indonesia, unemployment is one of the major challenges in the social and economic fields, with widespread impacts not only on individuals personally but also on social stability and overall economic growth. This study aims to analyze the influence of education level, wage level, and job opportunities on unemployment in Bali Province during the period of 2013-2023. This research uses an associative quantitative approach, as the data used is in numerical form, and data processing is performed through statistical analysis. The technique used in this study is panel data regression analysis to examine the impact of variables education, wages, and job opportunities on the variable unemployment. The results indicate that, simultaneously, education, wages, and job opportunities significantly affect unemployment in Bali Province, and individually, education, wages, and job opportunities also significantly affect unemployment in Bali Province. Education has a positive impact, while wages and job opportunities have a negative impact on unemployment in Bali Province.